DETERMINASI FAKTOR-FAKTOR YANG MEMPENGARUHI SUSTAINABLE BUSINESS PADA USAHA TENUN ENDEK DI KABUPATEN KLUNGKUNG - Putu Purnama Dewi; Ni Putu Lia Deniawati (Media Bina Ilmiah, 2025)
This study aims to determine the sustainable of endek weaving business in Klungkung, Bali. The research method used is quantitative research. The research location is in Klungkung, Bali. The data collection technique is using questionnaires. The data used is primary data to be obtained from the acquisition distribution. The number of samples used in this study was 85 respondents. The analysis technique uses multiple linear regression. The results show that green innovation and digital culture both partially and simultaneously have a positive and significant effect on sustainable business. Green human resource management is able to moderate the influence of green innovation on sustainable business and green human resource management is able to moderate the influence of digital culture on sustainable business.